PENGARUH PELAKSANAAN PRAKTIKUM INKUIRI BERBASIS LABORATORIUM VIRTUAL TERHADAP PENINGKATAN MOTIVASI DAN KREATIVITAS SISWA - Muzakkir Muzakkir; A Halim; Muhammad Syukri (Syiah Kuala University, 2015)
This study aims to determine the effect of the implementation of inquiry-based virtual lab laboratiorium to increase student motivation and creativity of students in simple harmonic motion of matter. The method used is the method of the control experiment with the design of the control group pre-test post-test. The study population was all students of class XI-IA, amounting to 180 people, and that the sample is class XI-4 as an experimental class IA and class XI-IA 1 as grade control at the school SMAN 5 Banda Aceh 2013/2014 school year. Data was collected using a form of written test of 20 multiple choice questions about done with the pre-test and post-test, student worksheets and questionnaires motivation and creativity of the student questionnaire. The results showed that the learning is done by using inquiry-based virtual lab laboaratorium. With the practical implementation of inquiry-based virtual laboratory has demonstrated that increasing students creativity in the material simple harmonic motion with mastery of concepts that are at 76.7% category and 23.3% higher category, the practical implementation of inquiry-based virtual laboratory can an increase student motivation in simple harmonic motion of matter. With the mastery of concepts that berkategorikan being, as well as 66% of student motivation is high enough and the remaining 34% is very high motivation.